A metadata schema to standardize non-thermal plasma decontamination parameters in food-related applications - George Pampoukis; Thomas Weihe; Robert Wagner; Markus Μ. Becker; Yijiao Yao; Masja N. Nierop Groot; Uta Schnabel (Scientific Data)
Abstract Non-thermal plasma research has gained significant attention as a promising technology for food-related decontamination. However, the lack of standardization in reporting key parameters restricts the applicability and reusability of results in this field. To address this, the present study introduces a metadata schema (MDS) that standardizes critical parameters and provides operational details for non-thermal plasma microbial inactivation in food-related applications. The metadata schema is implemented as an extension to Plasma-MDS, a metadata schema for plasma science, and aims to apply the FAIR (findable, accessible, interoperable, and reusable) data principles to food-related applications. The framework highlights relevant parameters related to the plasma source, the medium in which the plasma is ignited, the target (food-, and microbial-related parameters) treated with the plasma, and the diagnostic methods used to investigate these properties. Concrete examples of accurate metadata descriptions of all relevant parameter categories are provided in a human and machine-readable format to simplify adoption and dissemination. The introduced metadata schema strives to improve the comparability, reproducibility, and reuse of non-thermal plasma research data for food-related applications, paving the way for more generalizable insights to legal authorities and the food industry.